The association between razor clam consumption and memory in the CoASTAL cohort - Grattan, L.; Boushey, Carol; Tracy, K.; Trainer, V.; Roberts, S.; Schluterman, N.; Morris, J. (2016)
© 2016This study represents a preliminary effort to examine the potential impacts of chronic, low level domoic acid (DA) exposure on memory in the CoASTAL cohort over the first four years of data collection (Wave 1). Five hundred and thirteen adult men and women representing three Native American Tribes were studied annually with standard measures of cognition and razor clam consumption (a known vector of DA exposure) over a four-year period. In addition, a pilot metric of DA concentration exposure was used which took into consideration average DA concentration levels in source beaches, as well as the amount consumed. Based upon generalized estimating equations (GEE) analysis, controlling for age, sex, race, year, education level, tribe, and employment status, findings indicated that high razor clam consumers (15 or more per month) had isolated decrements on some measures of memory (p = 0.02–0.03), with other cognitive functions unaffected. The relatively lower memory scores were still within normal limits, and were thus not clinically significant. The pilot DA exposure metric had no association with any other aspect of cognition or behavior. There is a possible association between long-term, low-level exposure to DA through heavy razor clam consumption and memory functioning.